Candela Sdn Bhd / Deena Roslee... [et al.] - Roslee, Deena; Eging, Ferunica; Ahmad Shah, Muhamad Shahrezaa; Jabi, Noor Albannia Natasya; Jabi, Suhanah (2014)
Business is a basic ways to earn and gain money or income in all kinds of activities. Business can be vary, either products or services. Effectiveness and efficiency would affect the run of a particular business, and profit is the main goals in conducting a business. We chose to open up this business is because we found that there is lack of candle supply, and most of the products in local area were imported either from the Peninsular Malaysia or outside the country. Candle is an art form that has survived the centuries, borne out of necessity around 200AD. It usually used to illuminate space when there is the absent of light at night and during electrical power failure. Nowadays there are many function of candle, such as: aromatherapy, decoration, event gift, repellent and many more. The existing of Candela Sdn. Bhd provides all the current needs and wants of the candle today. We gain interest to build up this business after seeking the higher demand of candle not only for personal used as substitute light but for events purposes, for instance birthday party, wedding, religious ritual, candlelight dinner and et al. Other than that, candle which have repellent protection from insect are quite popular among the anti-insect repellent chemical consumers. Meanwhile, candle is semi-solid material that easier to reshapes and mixing with other added quality ingredients according to the desire and creativity of our company and customers to be. In Sabah there are only small amount of candle business and mostly homemade candle for decoration. Besides, the raw materials for making this product are abundance in Sabah. These factors trigger us to bringing the business into reality.